The Benefits of Lending Relationships: Evidence from Small Business Data - PETERSEN, MITCHELL A.; RAJAN, RAGHURAM G. (Journal of Finance, 1994)
ABSTRACT This paper empirically examines how ties between a firm and its creditors affect the availability and cost of funds to the firm. We analyze data collected in a survey of small firms by the Small Business Administration. The primary benefit of building close ties with an institutional creditor is that the availability of financing increases. We find smaller effects on the price of credit. Attempts to widen the circle of relationships by borrowing from multiple lenders increases the price and reduces the availability of credit. In sum, relationships are valuable and appear to operate more through quantities rather than prices.